A DISCOURSE ANALYSIS OF ENGLISH SWEARING WORDS USED IN AMERICAN MOVIES - Rahmawati Sukmaningrum; Faiza Hawa (ETERNAL (English Teaching Journal), 2022)
The purpose of this paper is aimed at giving a description of how English swear words, particularly in American movies, are used. The writers collect the common English swear words in American movies as the data. There are nine categories of English swear words. They are (1) sexuality, (2) eject and material from body, (3) family matters, (4) part of body, (5) blasphemy, (6) animal, (7) xenophobia, (8) low or bad personality, and (9) low status and profession. Among those categories, the most used terms are the English swear words from sexuality, eject and material from body, part of body and family matters. Considering the context of utterance, English swear words have four functions. They are; (1) as an abbreviation and short-hand of speaker’s distress, (2) as a means to insult or degrade someone, (3) as a means to achieve peer acceptance, and (4) as a means to stress the speaker’s utterance